Effect of botulinum neurotoxin type A (BoNTA) on the morphology and viability of 3T3 murine fibroblasts - Bandala, Cindy (Int J Clin Exp Pathol, 2015)
Aim: BoNTA is used in the treatment of ophthalmological disorders, muscular hyperactivity and pain. In recent years it has been described that BoNTA reduces cellular viability and induces apoptosis in prostate cells lines. Studies about the effect of BoNTA are no well known. There have been studies about the effect of BoNTA on the expression levels of collagenase in fibroblasts, but not on its morphological impact on these cells. The aim of this study was to determine the effect of BoNTA on the morphology and viability of the 3T3 fibroblast cell line. Material and methods: The 3T3 fibroblast cell line was cultured and the experimental group received 10 U BoNTA added to a 0.9% sterile saline solution in a reconstituted vial. The control group received saline solution only. Cultured cells were observed and photographed at 5, 10, 15 and 20 h. Cell viability was evaluated by means of the trypan blue test, and cell proliferation with the Proliferation Assay kit (PROMEGA). Results: The application of BoNTA to 3T3 fibroblast cells induced morphological changes, such as a loss of normal fibroblast morphology. Additionally, we observed the cytoplasmic retraction and spread phenomena. The nuclei showed other important changes with Giemsa staining. Conclusion: The results indicate that BoNTA induced a loss of spindle form, increase in cytoplasmic vesicles, and the presence of nuclear vesicles (compacted chromatin surrounded by a nuclear envelope). This suggests an apoptotic process and decreased cell viability. Further studies are needed to explore the mechanisms of these alterations.